Adding Perspective: Predicting Adolescent Sunscreen Use with an Extended Health Action Process Approach. Issue 2 (3rd April 2016) - Schüz, Natalie; Schüz, Benjamin; Eid, Michael
Abstract : Background: Diseases such as skin cancer often have a very long latency period. For adolescents, especially, it may be difficult to grasp that current risk behavior is related to future health outcomes. This study examines the role of health‐related time perspective (i.e. the degree to which short‐term outcomes are discounted over long‐time health benefits) within the Health Action Process Approach (HAPA). More specifically, based on expectancy*value theory, we tested whether time perspective interacts with self‐efficacy, the central variable in this approach. Methods: A longitudinal study with three measurement points across one year assessed 156 high school students. Data were analyzed using structural equation models. Results: While time perspective had no direct association with sunscreen use intentions, there was an interaction effect with self‐efficacy; the shorter the time perspective, the smaller the association of self‐efficacy with intention. Intention in turn predicted planning and sunscreen use at Time 3 (one year later). Conclusions: In order to maximise the impact of early onset measures for skin cancer prevention targeting the motivation for sunscreen use in adolescents, time perspective should be addressed in comprehensive sun protection interventions.